Idio maticity of English Terminology in Finance and Solutions for Finding Vietnamese Equivalents. M.A. Thesis Linguistics: 60 22 15 - Phạm, Phương Hoa (ĐHNN, 2017)
This thesis is intended to deal with idiomaticity of English financial terms, the difficulties they cause to translation and solutions for finding Vietnamese equivalents. Specifically, it studies the syntactic and semantic features of the terms which will (...)